2017
DOI: 10.1515/acve-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of rapidly forming severe oral lesions involving bacterial infection in a dog

Abstract: The term oronasal fistula refers to an acquired communication between the oral and nasal cavities, and can result from several conditions. However, oronasal fistula formation has not yet been described to be associated with bacterial infections. We have described in this case report for the first time a rapidly forming oronasal fistula and severe lingual lesions in a dog, involving an infection with Streptococcus canis. The patient was a 9-year-old male intact Golden Retriever with a nonspecific history of dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Histopathological features of canine NF in the current study are consistent with histopathological changes observed in previous reports of canine NF as well as NF in humans and mice 1,2,4–7,34–37 . After reviewing the medical records and available histopathological samples, it was evident that for many cases that did not meet our inclusion criteria, the term ‘necrotizing fasciitis’ reflected a pathological morphological diagnosis and not NF, the actual clinical entity or disease.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Histopathological features of canine NF in the current study are consistent with histopathological changes observed in previous reports of canine NF as well as NF in humans and mice 1,2,4–7,34–37 . After reviewing the medical records and available histopathological samples, it was evident that for many cases that did not meet our inclusion criteria, the term ‘necrotizing fasciitis’ reflected a pathological morphological diagnosis and not NF, the actual clinical entity or disease.…”
Section: Discussionsupporting
confidence: 89%
“…It is not clear if some of the same dogs were included in both of these reports. Other published case reports include both male and female dogs 1–4,6,7,10 . Although not statistically significant, intact animals were affected more frequently in the current study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation